Long-term Efficacy and Safety of Lamivudine, Entecavir, and Tenofovir for Treatment of Hepatitis B Virus-Related Cirrhosis - Koklu, Seyfettin; Tuna, Yasar; Gulsen, Murat Taner; Demir, Mehmet; Koksal, Aydin Seref; Kockar, Muhammet Cem; Baykal, Ozlem (Elsevier Science Inc, 2013)
BACKGROUND & AIMS: Data are limited on the efficacy and safety of tenofovir and entecavir when given for more than 1 year to patients with hepatitis B-related cirrhosis. We investigated the long-term safety and efficacy of these antiviral drugs in patients with chronic hepatitis B virus (HBV) infection, with compensated or decompensated cirrhosis, and compared results with those from lamivudine. METHODS: We performed a retrospective analysis of data from 227 adult patients with chronic HBV infection who were diagnosed with cirrhosis, beginning in 2005, at 18 centers throughout Turkey. There were 104 patients who had decompensated cirrhosis, and 197 patients were treatment naive before. Seventy-two patients received tenofovir (followed up for 21.4 +/- 9.7 mo), 77 patients received entecavir (followed up for 24.0 +/- 13.3 mo), and 74 patients received lamivudine (followed up for 36.5 +/- 24.1 mo). We collected data on patient demographics and baseline characteristics. Laboratory test results, clinical outcomes, and drug-related adverse events were compared among groups. RESULTS: Levels of HBV DNA less than 400 copies/mL were achieved in 91.5%, 92.5%, and 77% of patients receiving tenofovir, entecavir, or lamivudine, respectively. Levels of alanine aminotransferase normalized in 86.8%, 92.1%, and 71.8% of patients who received tenofovir, entecavir, and lamivudine, respectively. Child-Turcotte-Pugh scores increased among 8.5% of patients who received tenofovir, 15.6% who received entecavir, and 27.4% who received lamivudine. Frequencies of complications from cirrhosis, including hepatic encephalopathy, variceal bleeding, hepatocellular carcinoma, and mortality, were similar among groups. Lamivudine had to be changed to another drug for 32.4% of the patients. CONCLUSIONS: Tenofovir and entecavir are effective and safe for long-term use in patients with compensated or decompensated cirrhosis from HBV infection.
Keywords: Liver Function; Varices; Ascites; HCC Incidence